Berberine Suppresses Lung Metastasis of Cancer via Inhibiting Endothelial Transforming Growth Factor Beta Receptor 1 - Tian, Wenjia; Hao, Huifeng; Chu, Ming; Gong, Jingjing; Li, Wenzhe; Fang, Yuan; Zhang, Jindong; Zhang, Cunzheng; Huang, Yonghui; Pei, Fei; Duan, Liping (Frontiers in Pharmacology, 2022)
This study investigated the effects of berberine (BBR) on pancreatic cancer (PC) lung metastasis and explored the underlying mechanisms, using a BALB/C-nu/nu nude mouse model injected with PC cells (AsPC-1). Intragastric administration of BBR dose-dependently improves survival of mice intravenously injected with AsPC-1 cells, and reduces lung metastasis. Especially, BBR significantly reduces lung infiltration of circulating tumor cells (CTCs) 24 h after AsPC-1 cells injection. In vitro, tumor cells (TCs) trigger endothelial barrier disruption and promote trans-endothelial migration of CFSE-labeled TCs. BBR treatment effectively ameliorates TC-induced endothelial disruption, an effect that is diminished by inhibiting transforming growth factor-β receptor 1 (TGFBR1). Blocking TGFBR1 blunts the anti-metastatic effect of BBR in vivo. Mechanistically, BBR binds to the intercellular portion of TGFBR1, suppresses its enzyme activities, and protects endothelial barrier disruption by TCs which express higher levels of TGF-β1. Hence, BBR might be a promising drug for reducing PC lung metastasis in clinical practice.